Reading and playing musical notes with image processing techniques with mobile application - ERSOY, SEZGİN (My University, 2022)
The aim of this study is to process the notes on the music sheet, written by hand on the musical note line or edited in the computer environment, with the image processing technique and to play the music over the phone application. This application will be developed with Java in the Android Studio environment and image processing will be done using the OpenCV Library. Detection of a note will be memorized by calculating the value and duration of the note. After these sounds, the frequency values of the notes will be available on the phone.
Keywords: Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; Bilgisayar Bilimi Uygulamaları; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Computer Science Applications; Computer Science (miscellaneous); General Computer Science; Physical Sciences; mobil application; image processing; musical notes.